2009
DOI: 10.1088/0957-4484/20/39/395709
|View full text |Cite
|
Sign up to set email alerts
|

Probing the temperature dependence of the mechanical properties of polymers at the nanoscale with band excitation thermal scanning probe microscopy

Abstract: Understanding local mechanisms for temperature-induced phase transitions in polymers requires quantitative measurements of the thermomechanical behavior, including glass transition and melting temperatures as well as temperature dependent elastic and loss modulus and thermal expansion coefficients in nanoscale volumes. Here, we demonstrate an approach for probing local thermal phase transitions based on the combination of thermal field confinement by a heated SPM probe and multi-frequency thermomechanical dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 38 publications
1
61
0
Order By: Relevance
“…The PL spectrum taken on the manipulated QD is centred at 608 nm, and luminescence at this wavelength is completely absent elsewhere in the cell. The full-width at half-maximum (FWHM) of the QD spectra is 108 meV, which corresponds well to the previously studied emission from single colloidal quantum dots, for which PL blinking was recorded to optically identify the emission as being that from a single QD [2021]. Due to limitations in the collection optics it was not possible to see blinking in our sample.…”
Section: Resultssupporting
confidence: 79%
“…The PL spectrum taken on the manipulated QD is centred at 608 nm, and luminescence at this wavelength is completely absent elsewhere in the cell. The full-width at half-maximum (FWHM) of the QD spectra is 108 meV, which corresponds well to the previously studied emission from single colloidal quantum dots, for which PL blinking was recorded to optically identify the emission as being that from a single QD [2021]. Due to limitations in the collection optics it was not possible to see blinking in our sample.…”
Section: Resultssupporting
confidence: 79%
“…(6) and the error V 2ω by nonconstant TCR, V 2ω,raw = V 2ω,ideal + V 2ω,error . Equation (6) shows that V 2ω,ideal = 0 when η = 0, making V 2ω,raw = V 2ω,error when η = 0. For small η, V 2ω,error remains constant and the error can be corrected by finding V 2ω,error when η = 0 and then subtracting it from V 2ω,raw when η = 0.…”
Section: A Nonconstant Temperature Coefficient Of Resistancementioning
confidence: 99%
“…[3][4][5][6][7] Temperature calibration of heated AFM cantilevers is critically important for these and other applications. This article reports AFM cantilever temperature measurement and calibration under periodic heating.…”
Section: Introductionmentioning
confidence: 99%
“…The main difference between SThEM and TA-AFAM is a method used for excitation of contact resonance. [ 111 ] In case of SThEM, probe is heated with oscillating voltage and thermal expansion of the material under the tip drives contact resonance; in case of TA-AFAM, oscillations of the whole sample drives contact resonance while the probe is kept at constant temperature. While still in infancy, a number of studies have demonstrated mapping of melting and glass transition temperatures and dynamic thermomechanical characterization of polymer materials.…”
Section: Electromechanical Probesmentioning
confidence: 99%